Germanium redistribution during weathering of Zn mine wastes: Implications for environmental mobility and recovery of a critical mineral. (August 2022) - White, Sarah Jane O.; Piatak, Nadine M.; McAleer, Ryan J.; Hayes, Sarah M.; Seal, Robert R.; Schaider, Laurel A.; Shine, James P.
Abstract: Germanium (Ge) is a metal used in emerging energy technologies, communications, and defense, and has been deemed critical by the United States due to its essential applications and scarce supply. Germanium is recovered as a byproduct of zinc (Zn) sulfides, and mining and processing of these materials lead to waste that could act both as a source of extractable Ge and a source for exposure to humans and ecosystems. Yet the distribution, speciation, and mineral hosts of Ge in mining-impacted areas are poorly understood. The Tar Creek Superfund Site, a former Zn mining area and Ge producer, is a natural laboratory to understand the environmental behavior and economic implications of Ge in mine wastes. We studied the distribution and behavior of Ge in solid wastes at the Tar Creek Superfund Site using bulk and microanalytical techniques. In wastes at this site we find that Ge has been redistributed from its original host, sphalerite (ZnS), to the fine-grained weathering product hemimorphite (Zn4 Si2 O7 (OH)2 ·H2 O), which impacts germanium's mobility, bioaccessibility, and potential for recovery. We provide chemical and mineralogical evidence of this redistribution, along with an evaluation of the oxidation state and molecular-scale substitution of Ge into sphalerite, hemimorphite, and quartz. Geochemical modeling shows that hemimorphite is more stable than sphalerite in waste piles and provides a stable secondary repository for Ge. However, hemimorphite is fine-grained, and if ingested or inhaled is readily soluble, with the potential to release Ge. Lastly, we discuss other sites internationally where similar behavior may be important. This study shows that weathering can have a significant impact on the distribution, speciation, and mineral hosts of Ge in mine wastes; directly influence mobilization from waste piles and subsequent availability to humans and ecosystems; and dictate metallurgical strategies to target Ge for recovery. Graphical abstract: Image 1 Highlights: Weathering in mine wastes has altered mineral hosts and speciation of germanium (Ge). Ge exists in multiple oxidation states in sphalerite (ZnS), the original host mineral. Hemimorphite, a Zn-silicate weathering product, hosts majority of Ge. Presence in Zn-silicate has implications for mobility, bioavailability, and potential for recovery.